MATERNAL NUTRITIONAL STATUS AS A CONTRIBUTING FACTOR FOR THE RISK OF FETAL ALCOHOL SPECTRUM DISORDERS - May, Philip A. (Reprod Toxicol, 2015)
OBJECTIVE: Compare nutritional status of 57 South African mothers of children with fetal alcohol spectrum disorders (FASD) with 148 mothers of controls. METHODS: Dietary data were analyzed for macronutrients, micronutrients, and fats via Estimated Average Requirements (EAR) and Adequate Intakes (AI) for pregnant women. RESULTS: Virtually all mothers were likely deficient on most micronutrients by either EAR (<50%) or AI values. Mothers of FASD children consumed more of 13 of 25 micronutrients. For percentage below EAR, only vitamin D was significantly higher for FASD mothers. Despite no difference in total food intake, control mothers had a higher mean body mass index (BMI) than FASD mothers. Maternal BMI is more significant for positive child outcomes than any individual nutrient. CONCLUSIONS: Most mothers have inadequate dietary intake. Minor advantages in nutrient intake are overpowered by teratogenic effects of alcohol. Further study is needed of the interaction of alcohol, maternal nutrition, and metabolism.